2000
DOI: 10.1002/(sici)1097-0290(20000220)67:4<457::aid-bit9>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical fluid precipitation of recombinant human immunoglobulin from aqueous solutions

Abstract: Supercritical carbon dioxide was used as an antisolvent for producing recombinant human immunoglobulin G (rIgG) particulate powders. Liquid carbon dioxide (CO2) was premixed with ethanol to create a single‐phase, modified supercritical fluid (SCF). The modified SCF was then vigorously mixed with a pharmaceutically acceptable, aqueous formulation of rIgG, and the mixture was immediately atomized into a pressurized vessel where rapid expansion of the modified SCF extracted the aqueous phase, resulting in precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…This higher retained activity suggests that adding the cosolvent with the antisolvent, or precipitating proteins directly from an aqueous solution, may be a better microparticle formation technique than introducing an organic cosolvent in the aqueous phase. In comparison, retained activities of proteins precipitated from aqueous solutions by ethanol-enhanced CO 2 using the SEDS process have been reported as 95% for lysozyme (7) and 38-48% for rIgG (13). Winters et al (1) have reported recovered activity for lysozyme precipitated from DMSO solutions using liquid and supercritical CO 2 to range between 88 and 100% and between 89 and 99%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This higher retained activity suggests that adding the cosolvent with the antisolvent, or precipitating proteins directly from an aqueous solution, may be a better microparticle formation technique than introducing an organic cosolvent in the aqueous phase. In comparison, retained activities of proteins precipitated from aqueous solutions by ethanol-enhanced CO 2 using the SEDS process have been reported as 95% for lysozyme (7) and 38-48% for rIgG (13). Winters et al (1) have reported recovered activity for lysozyme precipitated from DMSO solutions using liquid and supercritical CO 2 to range between 88 and 100% and between 89 and 99%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Only recently has PCA been used to precipitate solutes in aqueous solutions, including organic salts (11), salicylic acid, lactose (12), recombinant IgG (13), lysozyme, rhDNase, insulin, albumin (14), and plasmid DNA (15). Although the proteins precipitated from these aqueous solutions were micronized, the considerable aggregation of the protein particles led to a loss of activity, with the exception of lysozyme and insulin micropowders (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty of applying gas antisolvent techniques to the processing of proteins is that they involve exposure of the protein to organic solvents, the latter being potential denaturants and very poor solvents for KONA No.l9 (2001) most therapeutic macromolecules. The ASES has been modified to enable the spraying of aqueous protein solution simultaneously with an organic solvent into carbon dioxide [24] or directly into carbon dioxide, which has been modified with an organic solvent [22,65].…”
Section: )mentioning
confidence: 99%
“…Recombinant human immunoglobulin (rhiG) [65], lysozyme [22], albumin, recombinant human deoxyribonuclease (rhDNase), insulin [22], trypsin [53], a therapeutic peptide antibody Fv and Fab and plasmid DNA [54] have been precipitated from aqueous based solutions. Except for rhiG, which was not obtained as a stable powder, all the proteins precipitated as micron-sized particles or agglomerated nano-spheres.…”
Section: )mentioning
confidence: 99%
“…6 A SEDS process has also been applied to the precipitation of an aqueous formulation of recombinant human immunoglobin G using carbon dioxide with dimethyl sulfoxide as a modified supercritical fluid anti-solvent. 7 Sievers and coworkers consistently obtained particles of various pharmaceutical agents, peptides and proteins, with mean particle sizes in the range of 0.1-3 µm, from their respective aqueous solutions through rapid decompression of emulsions formed by mixing the solutions with carbon dioxide. 8,9 Product particle sizes and their distributions could be controlled to some extent by varying concentration of the protein solution.…”
mentioning
confidence: 99%